A practical insulin infusion algorithm for the establishment of euglycaemia in both lean and obese patients with type 1 and type 2 diabetes. - Stork ADM; Erkelens DW; Veneman TF (Diabetes Research & Clinical Practice, 2006)
BACKGROUND: Both in research and in various clinical situations, prolonged euglycaemia can be desirable. In recent years, its benefit in (critically) ill patients and patients with acute myocardial infarction has been established. The objective of this study was to assess safety and efficacy of a practical, bodyweight-dependent algorithm to establish euglycaemia in both lean and obese patients with type 1 and type 2 diabetes. METHODS: In 43 patients with type 1 diabetes and 17 patients with type 2 diabetes insulin were infused overnight to establish euglycaemia. Plasma glucose concentration was determined at 45min intervals, and the insulin infusion rate was altered according to the algorithm. RESULTS: Baseline plasma glucose concentrations were 13.1+/-4.4 and 12.7+/-4.0mmol/l in type 1 and type 2 diabetic patients, respectively. In both groups mean plasma glucose was reduced below 8.0mmol/l within 3h, and averaged 7.4+/-1.4 and 7.2+/-1.0mmol/l (P=0.11) over the next 7h. Five (11.6%) patients with type 1 diabetes required administration of glucose because plasma glucose concentrations fell below 4.4mmol/l. Consequently, type 1 diabetic patients were hypoglycaemic during 0.89% of the total study period. The lowest plasma glucose recorded was 3.9mmol/l. In the type 2 diabetic patients the lowest plasma glucose was 5.5mmol/l and no glucose administration was required for near-hypoglycaemia. The algorithm was equally effective in both lean and obese patients. CONCLUSIONS: Euglycaemia was established simply, swiftly and safely during the study period with the practical weight-based algorithm used in this study, in both lean and obese type 1 and type 2 diabetic patients, with a very low rate of mild hypoglycaemia. The algorithm is applicable in research and various several clinical settings. Its validity for a prolonged period of time and in critically ill patients needs to be further evaluated.